EPR Spectroscopy Investigation of Cu2+ Ions Adsorbed in Tannin-Formaldehyde Resins of Mimosa (Acacia mearnsii) Bark Extracts - Marcelo H. Herbst; Ney V. Vugman (Journal of Spectroscopy)
The chemical environment of Cu2+ ions adsorbed in tannin-formaldehyde resins of Acacia mearnsii bark extracts, prepared from polybutene, is investigated by EPR spectroscopy at 300 K. The spectrum is simulated considering two isolated axial Cu(II) species (Species 1: A∥=16.50(5) mT, A⊥=1.20(10) mT, g∥=2.28(1), and g⊥=2.08(1); Species 2: A∥=15.00(5) mT, A⊥=1.50(10) mT, g∥=2.32(1), and g⊥=2.05(2)), superposed to a broad line (giso=2.14(1); linewidth = 30.0(5) mT) assigned to Cu(II) aggregates. Measurements at 77 K did not improve spectral resolution. Heating at 413 K changes the hyperfine parameters of Species 2 (A∥=14.20(5) mT, A⊥=1.20(10) mT, g∥=2.33(1), and g⊥=2.07(2)) and slightly modifies the parameters of the broad line (giso=2.11(2); linewidth = 40.00(50) mT) but does not change Species 1, assigned to Cu(II) species immobilized into resin pores in cathecolate-type coordination sites. Species 2 is assigned to Cu(II) species immobilized at the outer resin surface. Upon extended heating, a reversible formation of semiquinone-type paramagnetic radicals (giso=2.0037(1)) is observed, assigned to the partial collapse of the resin polymeric network.